Tumor infiltrating lymphocyte grade in Merkel cell carcinoma: relationships with clinical factors and independent prognostic value. (1st December 2020) - Yusuf, Mehran; Gaskins, Jeremy; Mandish, Steven; May, Michael E.; Wall, Weston; Fisher, William; Tennant, Paul; Jorgensen, Jeffrey; Bumpous, Jeffrey; Dunlap, Neal
Abstract: Introduction: Surrogate markers of the host immune response are not currently included in AJCC staging for Merkel cell carcinoma (MCC), and have not been consistently associated with clinical outcomes. We performed an analysis of a large national database to investigate tumor infiltrating lymphocyte (TIL) grade as an independent predictor of overall survival (OS) for patients with MCC and to characterize the relationship between TIL grade and other clinical prognostic factors. Material and methods: The NCDB was queried for patients with resected, non-metastatic MCC with known TIL grade (absent, non-brisk and brisk). Multivariable Cox regression modeling was performed to define TIL grade as a predictor of OS adjusting for other relevant clinical factors. Multinomial, multivariable logistic regression was performed to characterize the relationship between TIL grade and other clinical prognostic factors. Multiple imputation was performed to account for missing data bias. Results: Both brisk (HR 0.55, CI 0.36–0.83) and non-brisk (HR 0.77, CI 0.60–0.98) were associated with decreased adjusted hazard of death relative to absent TIL grade. Adverse clinical factors such as 1–3 positive lymph nodes, lymphovascular invasion (LVI) and immunosuppression were associated with increased likelihood of non-brisk TIL relative to absent TIL grade ( p values <.05). Extracapsular extension (ECS) was associated with decreased likelihood of brisk TIL relative to absent TIL grade ( p <.05). Discussion: Histopathologic TIL grade was independently predictive for OS in this large national cohort. Significant differences in the likelihood of non-brisk or brisk TIL relative to absent grade were present with regards to LVI, ECS and immune status. TIL grade may be a useful prognostic factor to consider in addition to more granular characterization of TIL morphology and immunophenotype.